Pelatihan Pembuatan Kunyit Instan Pada Ibu-Ibu Petani Jagung Di Dusun Pule Desa Kenongorejo Kecamatan Bringin - Endah Anggraini; Lutfiyatussolikhah; Erni Yuliatun; Rizkhi Ferdiansah; Evita Rosilia Dewi (Jurnal Abdikarya Pembangunan, 2024)
Abstract: Corn farming communities in Kenongorejo village need additional economic activities that can increase income. The selection of turmeric is based on asset analysis that shows the abundance of turmeric resources available on the land of Kenongorejo villagers. In addition, it also empowers mothers as the main drivers in improving the quality of health and family income. Community service activities use the ABCD approach that prioritizes community empowerment by utilizing existing assets. Training in making turmeric powder products for corn farming mothers in Pule hamlet, Kenongorejo village, Karangjati sub-district showed an increase in knowledge about the benefits of turmeric, as well as skills in making turmeric powder products and how to package the products when they are going to be sold. The training also provides social support for mothers to carry out healthy behaviors by consuming turmeric for family health. Further community service activities should provide assistance in the fields of marketing and product development so that the real impact on increasing community finances can be analyzed. Keywords: Corn Farmer, Instan Turmeric, Training, Abstract: Masyarakat petani jagung di desa Kenongorejo memerlukan tambahan kegiatanekonomi yang dapat menambah penghasilan. Pemilihan kunyit berdasarkan analisis aset yang menunjukkan keberlimpahan sumberdaya kunyit yang tersedia di lahan warga desa Kenongorejo.selain itu juga memberdayakan kaum ibu sebagai penggerak utama dalam peningkatan kualitas kesehatan dan penghasilan keluarga.Kegiatan pengabdian masyarakat menggunakan pendekatan ABCD yang mengutamakan pemberdayaan masyarakat dengan memanfaatkan aset yang dimiliki. Pelatihan pembuatan produk bubuk kunyit pada Ibu-ibu petani jagung di dusun Pule desa Kenongorejo kecamatan Karangjati menunjukkan adanya penambahan pengetahuan tentang manfaat kunyit , skill membuat produk kunyit instan, serta cara melakukan pengemasan ketika produk akan dijual. Pelatihan juga memberikan dukungan sosial pada ibu untuk melakukan perilaku sehat mengkonsumsi kunyit bagi kesehatan keluarga. Kegiatan pengabdian selanjutnya hendaknya melakukan pendampingan dalam bidang pemasaran dan pengembangan produk supaya bisa dianalisis dampak nyata bagi penambahan finasial masyarakat. Keywords: Kunyit Instan, Petani Jagung, Pelatihan